Political and economic drivers of Sudan's armed conflict: Implications for the agri-food system - Abushama, Hala; Resnick, Danielle; Siddig, Khalid; Kirui, Oliver K. (International Food Policy Research Institute, 2023)
This study assesses the political economy of the conflict between the Sudan Armed Forces (SAF) and the Rapid Support Forces (RSF) that brought out in April 2023, resulting in massive violence, displacement, and threats to food security. Based on a series of key informant interviews and other secondary materials, this study identifies that the primary underlying driver of the conflict relates to the rise of competition between the SAF and RSF over productive resources, including within the agri-food system. This scenario has been facilitated by a longstanding lack of scrutiny, accountability, and transparency over the distribution of economic rents and commercial holdings between the two factions. Additionally, the capture of rents from different industries and resources has been a key contributor to the geographic expansion of the conflict. As the conflict continues to rage between the two groups and their associates, it continues to impose considerable impacts on different actors within the agri-food system, posing significant challenges to the planting season and crop production, introducing blockades of trade routes, and a near cessation of agro-processing. We discuss these aspects of the ensuing conflict in view of the uncertainty about political and economic developments and propose policy recommendations for rebuilding Sudan’s agri-food system holistically under different scenarios.